A metal–organic framework film with a switchable anodic and cathodic behaviour in a photo-electrochemical cell. Issue 7 (21st November 2018) - Ifraemov, Raya; Shimoni, Ran; He, Wenhui; Peng, Guiming; Hod, Idan
Abstract : We show that a single MOF-based electrode can act as both a photo-anode and photo-cathode in a photo-electrochemical cell. Abstract : Photo-active metal–organic frameworks (MOFs) are considered as promising materials for the study of photo-electrochemical cells (PECs). They can be utilized as porous, high surface area scaffolds for the assembly of molecular chromophores atop semiconducting electrodes. Usually, however, the lack of prominent electronic interactions between adjacent MOF-installed chromophores impedes the development of PECs based solely on MOFs (without the use of a semiconducting electrode, e.g. TiO2 ). Here we demonstrate that unlike standard semiconducting photo-electrodes, the photo-electrochemical behavior of a MOF-based electrode can be switched from photo-anodic to photo-cathodic by using appropriate redox mediators in the electrolyte. Additionally, a proof-of-principle photo-electrocatalytic H2 production using a MOF-based photo-cathode is provided. Thus, these findings have a clear impact on the design of MOF-based PECs for solar fuel generation.